Film og samfund - Laustsen, Carsten Bagge (Slagmark - Tidsskrift for idéhistorie, 2018)
The article is an investigation of the relation between social studies and movies and in turn the relevance of movies to the social sciences. The relationship between the world of movies and reality is analyzed through the movies Being there and Storytelling. Three different approaches are presented: The movie society, socio-fiction and movies as ambiguos cultural products.